Other people's worlds an introduction to cultural and social anthropology - Hendry, Joy (New York University Press, 1999)
"Other People's Worlds offers the perfect introduction to cultural and social anthropology for anyone approaching the subject for the first time. Hendry introduces classic theoretical ideas of the key founders of cultural and social anthropology, placing them in their historical and geographical context. Carefully structured so that one chapter builds on the next, Other People's Worlds covers the core topics in an even-handed and illuminating manner, introducing the reader to divergent views on all the most basic subjects - food, hygiene, gift-exchange, rites of passage, symbolism, religion, politics, and the environment - and raising awareness of the emotional value people place on those views. Covering a wide array of countries, it brings the subject of cultural and social anthropology right into the neighborhood of the reader, wherever they are in the world."